Methods of teaching the discipline «Style and literary editing» (Eurasian Journal of Philology Science and Education, 2016)
The article deals with the methods of teaching the subject «Style and literary editing» as a practical discipline for future journalists, studying professional techniques of the editor in preparing the text of a literary work for publication in print, on radio and television. The article states that the formation of literary editing both an academic and practical discipline in the system of journalism education is associated with the theoretical basis of literary editing. The detailed exposition of the object of editing as a method to enhance the information requirements, efficiency, requirements to them is given in addition to the material. The social meaning of editorial work in the context of globalization is developed as a means to improving its effectiveness, as one component of the profession of journalism and the unity of the ideological, scientific and literary aspects of the editor. Editing features in mass-media condition (newspapers, radio, television) are presented as the specifics of editorial work on text material for news agencies.
Keywords: editing; mass-media; editor; style; composition.